EQUIPPING THE YOUTH BY RECOURSE TO THE TOTAL LIFE TRAINING TOOL FOR YOUTH CHALLENGES IN CHRISTIANA: - F.E. Freeks (Acta Theologica)
In South Africa, the youth face immense challenges and problems. Farming communities in Christiana grapple with problems such as unemployment, poverty, occultism, Satanism, alcoholism and violence. The challenges for this specific community are widespread, because they encounter one problem after another, on the one hand, and increasing statistics of social ills such as prostitution, child-trafficking, substance use and abuse, violence and rape, on the other. As a consequence, numerous young people’s lives are being destroyed. My current study focuses on the youth of the Christiana District in South Africa as target for a holistic missional outreach programme. The purpose of the study is to give hope, build resilience, and improve or enhance the lives of young people through the TOTAL LIFE programme, despite the challenges they are facing daily. This missional and biblical tool is designed in a constructive, creative-critical way, from a missio Dei perspective.